Low Cost DTM for Certain Engineering Purposes - Matori, A.N (2010)
Digital Terrain Model (DTM) is a representation of an earth surface in the three-dimensional form. The need to study DTM is to improve its accuracy and efficiency. There are three types of DTM which are contour lines, grid model and triangulated irregular network (TIN) model where each one has its own characteristics depending on the purposes of the DTM. Total station is often used in acquisition of terrain data for the DTM due to its practicality (depending upon weather condition) and easier to use albeit labor intensive. For this study, DTM is produced based on the selected study area and the generated DTM will be used to simulate preliminary engineering practice during construction such as cut and fill and certain hydrology simulation. To generate DTM, terrain data is acquired through using Total Station. The data is used as to produce the terrain model using TIN method. The model is analysed based on several aspects. Area with major change in slope requires higher density of data to describe the feature of the slope changes. Different pattern data distribution can also be seen in different DTM with different feature requirement. Different types of terrain have different effects on the DTM production. In the end of this study the accuracy of this Low Cost DTM and its applicability for engineering purposes will be assed.